Measurement and cancellation of light shift in optically pumped magnetometers. (18th May 2018) - Li, Rujie; Quan, Wei; Fan, Wenfeng; Fang, Jiancheng
Abstract: Light shift arising from the circularly polarized pump beam in atomic magnetometers can induce an undesired magnetic response, and thus affect their accuracy. Here, the light shift and the corresponding cross-talk effect in the magnetometer have been investigated, and a scheme with an additional off-resonant pump beam with an appropriate polarization and intensity has been proposed to effectively reject the light shift. And the experimental results reproduce the expected behavior. This scheme provides a powerful tool to reject the light shift in optical pumping systems, in particular, the hybrid optically pumped systems.